Bilirubin nanoparticles ameliorate allergic lung inflammation in a mouse model of asthma. (September 2017) - Kim, Dong Eon; Lee, Yonghyun; Kim, MinGyo; Lee, Soyoung; Jon, Sangyong; Lee, Seung-Hyo
Abstract: Although asthma, a chronic inflammatory airway disease, is relatively well-managed by inhaled corticosteroids, the side effects associated with the long-term use of these agents precipitate the need for alternative therapeutic options based on differing modes of action. Bilirubin, a potent endogenous antioxidant, and anti-inflammatory molecule have been shown to ameliorate asthmatic symptoms; however, its clinical translation has been limited owing to its water insolubility and associated potential toxicity. Here we report the first application of bilirubin-based nanoparticles (BRNPs) as a nanomedicine for the treatment of allergic lung inflammatory disease. BRNPs were prepared directly from self-assembly of PEGylated bilirubin in aqueous solution and had a hydrodynamic diameter of ∼100 nm. Because allergen-specific type 2 T-helper (Th2) cells play a key role in the pathogenesis and progression of allergic asthma, the effects of BRNPs on Th2 immune responses were investigated both in vivo and in vitro . BRNPs after intravenous injection (i.v.) showed much higher serum concentration and a longer circulation time of bilirubin than the intraperitoneal injection (i.p.) of BRNPs or unconjugated bilirubin (UCB). The anti-asthmatic effects of BRNPs were assessed in a mouse model of allergen-induced asthma. Compared with UCB, treatment with BRNPs suppressed the symptoms of experimental allergic asthma and dramatically ameliorated Th2-related allergic lung inflammation. Consistent with these results, BRNPs caused a reduction of Th2 cell populations and the expression of related cytokines by antibody-stimulated CD4 + T cells in vitro . Therefore, our results establish BRNPs as an important immunomodulatory agent that may be useful as a therapeutic for allergic lung inflammatory disease and other immune-mediated disorders.